Kartu Peserta Badan Penyelenggara Jaminan Sosial Kesehatan Sebagai Salah Satu Syarat Peralihan Hak Atas Tanah Dalam Perspektif Hukum Administrasi - Maria Monika Laklo; Yohanes G. T. Helan; Yorhan Yohanis Nome (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The BPJS Health Participant Card used as one of the conditions for the transfer of land rights in Presidential Instruction Number 1 of 2022 ratified by President Jokowi is a provision that raises pros and cons in various circles because it contradicts PP Number 24 of 1997. This research was conducted with the aim of knowing the reasons for the BPJS Health Participant Card to be used as one of the requirements for legal force for the transfer of land rights and the process of transferring land rights using the BPJS Health Participant Card. The type of research used is normative research, which is normative research carried out by collecting legal materials with literature studies in the form of books, law journals and laws and regulations: (1) The reason why the BPJS Health Participant Card is used as one of the conditions for transferring land rights is intended as a way to optimize the implementation of the National Health Insurance as written in INPRES Number 1 of 2022. However, PP Number 24 of 1997 does not explain or mention that the BPJS Health Participant Card is used as one of the conditions for transferring land rights. This makes Presidential Instruction Number 1 of 2022 contradict PP Number 24 of 1997, (2) The process of transferring land rights has not changed, it only needs to add a photocopy of the active BPJS Health Participant Card. If you do not include a photocopy of the BPJS Health Card, the land title transfer document will be held until you submit the requirement.